2020
DOI: 10.2147/clep.s256735
|View full text |Cite
|
Sign up to set email alerts
|

<p>Statistical Analysis of Clinical COVID-19 Data: A Concise Overview of Lessons Learned, Common Errors and How to Avoid Them</p>

Abstract: By definition, in-hospital patient data are restricted to the time between hospital admission and discharge (alive or dead). For hospitalised cases of COVID-19, a number of events during hospitalization are of interest regarding the influence of risk factors on the likelihood of experiencing these events. The same is true for predicting times from hospital admission of COVID-19 patients to intensive care or from start of ventilation (invasive or non-invasive) to extubation. This logical restriction of the data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 30 publications
0
46
0
1
Order By: Relevance
“…Since the number of studies on COVID-19 treatment effectiveness and the speed of publishing new data in journals has drastically increased [32], unbiased results from observational studies are extremely important as a complement to randomized controlled trials. The methodological challenges in studying observational COVID-19 data and performing statistical analysis on drug effectiveness has been already described in detail [33,34]. However, our review has demonstrated that methodological issues such as immortal time bias, confounding bias and competing risk bias are commonly found in articles published in high-impact medical journals.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Since the number of studies on COVID-19 treatment effectiveness and the speed of publishing new data in journals has drastically increased [32], unbiased results from observational studies are extremely important as a complement to randomized controlled trials. The methodological challenges in studying observational COVID-19 data and performing statistical analysis on drug effectiveness has been already described in detail [33,34]. However, our review has demonstrated that methodological issues such as immortal time bias, confounding bias and competing risk bias are commonly found in articles published in high-impact medical journals.…”
Section: Discussionmentioning
confidence: 85%
“…As the primary step, a complete competing risk analysis should be presented that includes a cause-specific Cox regression analysis for the event of interest and for all competing events [7,33,36,37]. An initial model should include baseline covariates, further, time-fixed confounders need to be adjusted.…”
Section: Discussionmentioning
confidence: 99%
“…For this analysis, cumulative incidence graphs and estimates were obtained using death as event of interest and discharge alive as competing risk. 5 Patients who did not die by the end of the study period and were not discharged alive were censored at the time of last clinical follow-up.…”
Section: Methodsmentioning
confidence: 99%
“…Analyses that stratify patients by in-hospital statin use are subject to both immortal time bias and time-varying confounding, as a patient’s changing health condition affected when and whether they initiated statins ( 28 ). To address these challenges, we used marginal structural Cox proportional hazards models to evaluate the effect of statin initiation on the primary and secondary outcomes ( 29 ).…”
Section: Methodsmentioning
confidence: 99%